Pelatihan Peningkatan Kemampuan Membaca Bahasa Arab (Maharah Qira’ah) pada Santri di Pesantren Berbasis Tematik - Zainuri Zainuri; Siti Nurjanah (An-Nuqthah, 2026)
This community service aims to improve Arabic reading skills (maharah qira’ah) among beginner santri at MAN I JEMBERJember through participatory tutoring combined with intensive guided reading practice over eight sessions. Using a participatory design involving pre-post tests, observation, and thematic analysis, results reveal a significant improvement in average scores from 45 to 84 (an 86% increase), particularly in reading fluency, word recognition, and comprehension of simple texts. The findings are influenced by repetitive exposure, scaffolding strategies, and reduced anxiety in a supportive learning environment. This model demonstrates effectiveness for non-formal Arabic learning in vocational pesantren, though limited by a small sample size.